Hunter's Heart Ridge : a mystery - Taylor, Sarah Stewart (A Franklin Warren and Alice Bellows mystery, 2025)
"In this sequel to Taylor's lyrical series debut, Agony Hill, Detective Frank Warren and his formerly CIA-connected neighbor Alice Bellows return to investigate the death of a diplomat. It's November of 1965 and the second weekend of Vermont's regular deer season when Vermont State Police detective Franklin Warren is called out to what looks like an accidental shooting at The Ridge Club, an exclusive men's hunting and fishing club for congressmen, diplomats, judges, and titans of industry: a former ambassador has been shot while out hunting. With the war in Vietnam picking up speed on the other side of the world, Warren quickly realizes that many of the club's members are powerful men who may have ulterior motives and connections in high places. While Warren's suspicions about the club members build, his neighbor Alice Bellows is throwing a dinner party, preparing for Thanksgiving, and worrying about her pregnant friend and fellow widow, Sylvie Weber, whose due date is coming up. When Alice's old handler and friend, Arthur Crannock, unexpectedly shows up in Bethany, Alice begins to wonder whether his presence has anything to do with the death at the hunting club. As an early season snowstorm bears down on Bethany, knocking out power and phone lines and blocking the roads, Warren and his assistant, Trooper Pinky Goodrich, are trapped at the Ridge Club, likely along with a killer, and Alice, increasingly fearful that her past in the intelligence world is no longer in the past, will have to act fast to save Sylvie and her baby. Sarah Stewart Taylor's historical series combines the intricacy of a satisfying mystery with keen observation of a time and place during great transformation and upheaval"--